2021
DOI: 10.3389/fped.2021.705663
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Cut-Off Values of Scoring System for Diagnosis of Hirschsprung-Associated Enterocolitis After Transanal Endorectal Pull-Through

Abstract: Background: Hirschsprung-associated enterocolitis (HAEC) is a major contributor in the mortality of Hirschsprung disease (HSCR) patients that can occur both preoperatively and post-operatively. Several cut-off values of HAEC score have been used, i.e., ≥10 and ≥4. Here, we compared the HAEC frequency after transanal endorectal pull-through (TEPT) using two cut-offs of scoring system and associated them with the risk factors.Methods: Cross-sectional analysis was conducted using medical records of HSCR patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…A retrospective study reported by Du Juan 36 also indicated that malnutrition is a risk factor for the occurrence of enterocolitis in children with congenital megacolon after surgery. A recent retrospective study 37 identified microcytic hypochromic anemia as a risk factor for postoperative HAEC, but our cohort study did not find a significant association between hemoglobin levels and postoperative HAEC. In this study, other markers such as CRP, PCT, and hemoglobin did not show a significant association in regression analysis, consistent with the conclusions of our study.…”
Section: Discussioncontrasting
confidence: 97%
“…A retrospective study reported by Du Juan 36 also indicated that malnutrition is a risk factor for the occurrence of enterocolitis in children with congenital megacolon after surgery. A recent retrospective study 37 identified microcytic hypochromic anemia as a risk factor for postoperative HAEC, but our cohort study did not find a significant association between hemoglobin levels and postoperative HAEC. In this study, other markers such as CRP, PCT, and hemoglobin did not show a significant association in regression analysis, consistent with the conclusions of our study.…”
Section: Discussioncontrasting
confidence: 97%
“…The definition used in this study for Hirschsprung-associated enterocolitis (HAEC) is the Frykman modification of the Pastor score, with a cut-off value of 4 [1,4]. The HAEC score contains information on patient history, physical and radiological examination, and laboratory results, with a maximum value of 20 [1,4].…”
Section: Postoperative Bowel Managementmentioning
confidence: 99%
“…Approximately 30% of HD patients will experience at least one episode of HAEC. Note, however, that there is currently no consent on the exact definition of HAEC [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…These aspects should be considered while interpreting our findings. In addition, we have not included enterocolitis as persistent obstructive symptoms since we have already specifically determined the prognostic factors for enterocolitis in our previous studies [23,24].…”
Section: Plos Onementioning
confidence: 99%